2018
DOI: 10.24093/awej/vol9no2.5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ECRIF Strategy on EFL Seventh Graders’ Vocabulary Learning and Retention

Abstract: This paper aims at highlighting the effectiveness of Encounter, Clarify ,Remember, Internalize, Fluent Use (ECRIF) strategy in English as a Foreign Language (EFL) Seventh Graders' vocabulary learning and retention. It tries to answer the following question : Are there statistically important differences at (α ≤ 0.05) in the whole mean scores in vocabulary accomplishment among the students who learn English vocabulary through using ECRIF strategy (experimental group) and those who learn English vocabulary over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The findings showed that using WhatsApp to hone writing abilities was recommended for EFL students. Alsaleem (2013) executed a quantitative, quasi-experimental study to assess the impact of integrating WhatsApp electronic journaling as a new smartphone application on Saudi Arabian undergraduate students' writing skills, word selection, and voice expression. Saudi Arabian undergraduate EFL learners were among the participants in the study.…”
Section: Iranian Undergraduate Efl Learnersmentioning
confidence: 99%
“…The findings showed that using WhatsApp to hone writing abilities was recommended for EFL students. Alsaleem (2013) executed a quantitative, quasi-experimental study to assess the impact of integrating WhatsApp electronic journaling as a new smartphone application on Saudi Arabian undergraduate students' writing skills, word selection, and voice expression. Saudi Arabian undergraduate EFL learners were among the participants in the study.…”
Section: Iranian Undergraduate Efl Learnersmentioning
confidence: 99%
“…Most items related to learning spoken English, such as pronunciation, word meaning, synonyms, and usage, can be found on one platform. Various applications of personal and professional conversations, dictionaries, and thesauruses have contributed to the enhancement of spoken English of innumerable learners globally (Alsaleem, 2013;Godzicki et al, 2013).…”
Section: Rq1: What Are the Specific Spoken English Difficulties Encou...mentioning
confidence: 99%
“…Furthermore Mezied (2017) and AlSaleem (2018), state that ECRIF shows a positive impact on students as it is a great strategy to teach vocabulary and improve memory retention which is particularly necessary when speaking a language. Finally important, Eker (2020) points out that ECRIF has a taxonomic structure like Blooms taxonomy where each stage pursues a hierarchical model where the learning objective is classified into levels of complexity and specificity.…”
Section: Introductionmentioning
confidence: 99%